Bases atencionais do raciocínio emocional infantil em contextos sociais - Reis, Aline Henriques (2007)
Studies about emotional reasoning and parent-based reasoning had found that the emotional reply to fear in children evaluated through experimental task of script danger assessment happens as in relation to danger information, as safety information contained in them. Nevertheless, the attentional bias (psychopatological process which implies in selection of distorted information) has been investigated apart from emotional reasoning. Therefore, the aim of this work is to rate emotional reasoning in social contexts mediated by the parents or by peers at the same age and to correlate this task-based performance with the level of social skills measured through Multimedia System of Social Skills and also with the performance in the stroop selective attention task from those children. For this purpose children, from 8 to 12, were rated from one private school from Uberlândia (N=59) to test the hypothesis that emotional reasoning in childhood is a natural phenomenon of emotional and cognitive development. To analyse the data, parametric variance tests and correlations of the evaluated measures were used. The results had shown the occurrence of the emotional reasoning and parent-based emotional reasoning, Considering that the sample not only trusted in the dangerous information contained in scripts, but took the anxiety reply to figure the situation as dangerous or not. In this way, in the types of answers analysis (positive or anxiety ones) it was observed that the tales with anxiety reply information (M= 1,8) had been evaluated as more dangerous than the tales with positive reply information (M= 0,97) with F [(1,482) = 25.571, P <0.0001]. The Stroop task got an effect on the types of stimulation shown F [(2,98) = 161,894, P < 0.0001], however, this effect is not caused due to an attentional bias, but to a difference between neutral and emotional stimulations (18,22seg. e 17,59 respectively,) in relation to the controlled condition (13,49 second). Also the series effect was significant [F (8,98) =5,498, p < 0.001], considering that the second series spent significantly more time, in every condition, among all the series. In the Social Skills test, the girls had shown greater level of social skills compared to the boys and the variable social skill was correlated with many evaluated experimental conditions in the study. Similar to other studies this one also confirmed the occurrence of emotional reasoning and the parent-based emotional reasoning as a normal childhood phenomenon, it had shown that in its support, the interpretation bias and not the atencional bias can be found.